1999
DOI: 10.1034/j.1398-9995.1999.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin lispro, an alternative in insulin hypersensitivity

Abstract: References 1. Dhaliwal A, Fink J. Vaginal itching as a manifestation of seasonal allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…Rapid-acting insulin analogues revealed with an immediate dissociation of hexamer structure to monomers, so that they might be less antigenic [38,39]. Successful treatment of local and systemic insulin allergy has been reported with switching of insulin treatment to a rapidacting insulin analogue, namely insulin lispro [40][41][42][43], aspart [44,45] or glulisine [46]. In a series of 22 patients with insulin allergy, Bodtger et al [12] reported five patients treated with insulin analogues, of those three had full and two had partial remission.…”
Section: The Use Of Insulin Analoguesmentioning
confidence: 98%
“…Rapid-acting insulin analogues revealed with an immediate dissociation of hexamer structure to monomers, so that they might be less antigenic [38,39]. Successful treatment of local and systemic insulin allergy has been reported with switching of insulin treatment to a rapidacting insulin analogue, namely insulin lispro [40][41][42][43], aspart [44,45] or glulisine [46]. In a series of 22 patients with insulin allergy, Bodtger et al [12] reported five patients treated with insulin analogues, of those three had full and two had partial remission.…”
Section: The Use Of Insulin Analoguesmentioning
confidence: 98%
“…Especially in patients that show allergic reactions to components of the preparation a switch to a preparation which does not contain the specific agent can lead to a cessation of symptoms (16). To offer alternatives to the patient allergic to insulin analogues, lispro, aspart and glargine with the exchange of two (B28‐proline and B29‐lysine), one (B28‐aspartate) or the exchange of one (A21‐glycine) and addition of two amino acids (B31‐arginine and B32‐arginine), respectively, have been used (17–20). Although these represent options for patients with allergy to insulin (21) they have also been known to provoke hypersensitivity reactions including type 1 allergies in clinical practice (22–25).…”
Section: Managementmentioning
confidence: 99%
“…Anecdotal reports suggested local and generalized allergy to human insulin could be successfully treated with insulin lispro [45][46][47][48][49] or with insulin aspart [49][50][51]. In the series of 22 cases published by Bodtger et al [26], 5 patients were treated with insulin analogues, among whom 3 with a clear success and 2 with partial improvement.…”
Section: Insulin Analogues and Insulin Allergymentioning
confidence: 99%